The War, French National Guards, Gardes Mobiles, Pompiers, and Volunteers. - Robert Landells (Wikimedia Commons, 1870)
Notice iconographique issue de Wikimedia Commons. Titre: The War, French National Guards, Gardes Mobiles, Pompiers, and Volunteers.. "The [Franco-Prussian] War: French National Guards, Gardes Mobiles, Pompiers, and Volunteers." Illustration for The Illustrated London News, 3 September 1870. Author: Mr. Landells (See the text in Image:Crown Prince Frederick William of Prussia - Illustrated London News August 20, 1870.PNG, which mentions a Mr. Landells as at least one of the Special Artists for the Illustrated London News in France at the time.)
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; Patrimoine; Wikimedia Commons; Iconographie